Congenital stationary night blindness - Kocyła-Karczmarewicz, Beata; Grałek, Mirosława; Juszko, Jadwiga; Trzebicka, Agnieszka; Sarti, Grażyna (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Authors present diagnostic procedures and clinical features of the congenital stationary night blindness (CSNB) in 19 patients. Effective therapy of the concomitant ophthalmological pathologies usually improves patient's vision ability.